Increasing the Advantages of Home-Based Tempeh Chips Business Using SWOT Analysis - Putra Mulyana, Andrea (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Every business entity must be prepared to face fierce competition to maintain its position in the market. The diverse range of business sectors demands entrepreneurs to continuously enhance their competitiveness to sustain profitability and thrive in a dynamic environment, including Tempe Chips producers. Through SWOT analysis, entrepreneurs can identify internal strengths to build competitive advantages. Hence, the author is interested in researching this aspect to understand the role of SWOT analysis in enhancing the competitive edge of homemade tempeh chips. The research method employed is qualitative descriptive with a literature review. The findings indicate that SWOT analysis enables companies to holistically evaluate their market position by considering internal and external factors affecting their business. With a better understanding of strengths, weaknesses, opportunities, and threats, companies can identify appropriate strategies to leverage their strengths, address weaknesses, and capitalize on market opportunities.